Nodulation, yield and quality of soybean as influenced by integrated nutrient management - Alam, MA; Siddiqua, A; Chowdhury, MAH; Prodhan, MY (Journal of the Bangladesh Agricultural University, 2010)
A field experiment was conducted at the Horticultural Farm of Bangladesh Agricultural University, Mymensingh during the period from November 2007 to March 2008 to study the effect of integrated nutrient management on nodulation and sustainable soybean production. There were significant differences among the different treatment combinations in terms of yield and yield contributing characters. Integrated nutrient management with application of 50% of the recommended doses of urea, TSP, MOP, gypsum and biofertilizer (Bradyrhizobium) at the rate of 1 kg ha-1 significantly increased most of the parameters, such as the highest plant height, number of nodule per plant, nodule dry weight per plant, pods per plant, grains per pod, grain yield, oil and protein contents. Coinoculation of Bradyrhizobium seemed to help reduce the NPKS requirement in soybean cultivation. Overall results indicate that the application of integrated nutrient management of biofertilizer (Bradyrhizobium) with ½ NPKS of the recommended dose would produce the best quality of soybean with higher nodulation and yield. Keywords: Nodulation; Integrated nutrient management; Inoculation DOI: 10.3329/jbau.v7i2.4723 J. Bangladesh Agril. Univ. 7(2): 229-234, 2009